EVALUASI PENGGUNAAN PLATFORM CANVA PADA PENGGUNA PEMULA BERDASARKAN ISO/IEC 25010: STUDI DESKRIPTIF KUANTITATIF - Achmad Rezy Aprian Nafi; Bagas Dwi Anggoro Setyo Wibowo; Aldi Firmansyah; Khanif Nur Hidayat; Dendy Kurniawan (CV. Denasya Smart Publisher, 2026)
Canva has become one of the most popular cloud-based graphic design tools in Indonesia with millions of active users from various backgrounds. Despite the continuous growth of Canva usage, there has been no comprehensive research measuring the quality of this platform using structured international standards. This study aims to evaluate the usability of Canva platform based on ISO/IEC 25010 standards, focusing on four quality characteristics: Usability, Functional Suitability, Performance Efficiency, and Reliability. The research method employed is a descriptive quantitative approach using survey technique involving 56 active Canva users in Indonesia. The research instrument consists of a structured questionnaire with 17 closed statements using a 5-point Likert scale and 2 open-ended questions to capture qualitative insights. Data were analyzed using descriptive statistics and thematic analysis for qualitative data. The research results indicate that Canva platform has good quality with an overall average score of 3.90 out of 5.00. Usability characteristic obtained the highest score of 4.04, categorized as very good, followed by Functional Suitability with a score of 3.98. Meanwhile, Performance Efficiency and Reliability obtained scores of 3.77 and 3.80, categorized as good. Qualitative analysis identified that the main user complaints were performance and speed issues (25 percent) and limited free features (13,6 percent). This study concludes that Canva's main strengths lie in usability and functional suitability, but significant improvements are needed in performance and system reliability aspects to enhance overall user satisfaction.